The gender differences in highly paid wage: A case study of peruvian physicians - Amaya Chunga, Elard (2019)
In recent decades, the number of women pursuing careers in health has significantly increased. However, the physician labor market is still characterized by gender differences regarding payment. Using a nationally representative Peruvian sample of health providers (3,219 male and 1,063 female physi-cians), we estimated the gender gap in the likelihood of earning high wages for physicians and decomposed this gap in a proportion related to differences in individual characteristics (e.g. specialty, labor experience), and a residual proportion related to differences in returns to these characteristics. Our main results reveal that male physicians have on average an 81% higher likelihood of earning high salaries (monthly earning level > 5,000 PEN) relative to their female counterparts. Further, the main proportion of this gap is associated to the unexplained component (among 57% and 77%, according to the model specification), which may be associated to unobservable characteristics and discrimination in the Peruvian labor market.